2013
DOI: 10.1007/s10753-013-9760-6
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Fatty Acids Up-regulate COX-2 Expression in Prostate Epithelial Cells via Toll-like Receptor 4/NF-κB Signaling

Abstract: Cyclooxygenase-2 (COX-2) has been implicated in prostate carcinogenesis, and recently it has been confirmed to be a molecular target of saturated fatty acids (SFAs). In the present study, we investigated the effect of stearic acid (SA) and palmitic acid (PA), two of the most abundant SFAs contained in dietary fat, on COX-2 expression in prostate epithelial cells and the signaling transduction pathway involved. First, we demonstrated that both SA and PA increased the mRNA and protein expression of COX-2, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…35 Both stearic acid and palmitic acid induce the activation of NF-κB and stimulate the secretion of pro-inflammatory mediators in trophoblast cells isolated from human placentas, 36,37 microglial cells, 38 and prostate epithelial cells. 39 Similarly, palmitic acid significantly activates JNK in HEPG2 cells; 40 increases the expression of MCP-1 in mesangial cells; 15 induces the expression of IL-6, IL-8, and MCP-1 in smooth muscle cells; 41,42 increases the activation of p38, JNK, and NF-κB with enhanced expression of TNFα in C2C12 skeletal muscle cells; 43,44 enhances the activation of NF-κB with increased production of IL-6 and TNF-α in adipocytes; 23,45 and induces the activation of p38, ERK, and JNK with increased expression of COX-2, IL-6 and MCP-1 in fibroblast cells. 46,47 Dietary supplementation with high-fat diet (HFD) or infusion of Liposyn II (a 20% triglyceride nonpyrogenic emulsion), lipid/heparin, soybean oil, lard oil, or fatty acids has been used to increase circulating FFA level in human and animal model studies.…”
Section: Long-chain Sfas Increase the Production Of Inflammatory Medimentioning
confidence: 99%
“…35 Both stearic acid and palmitic acid induce the activation of NF-κB and stimulate the secretion of pro-inflammatory mediators in trophoblast cells isolated from human placentas, 36,37 microglial cells, 38 and prostate epithelial cells. 39 Similarly, palmitic acid significantly activates JNK in HEPG2 cells; 40 increases the expression of MCP-1 in mesangial cells; 15 induces the expression of IL-6, IL-8, and MCP-1 in smooth muscle cells; 41,42 increases the activation of p38, JNK, and NF-κB with enhanced expression of TNFα in C2C12 skeletal muscle cells; 43,44 enhances the activation of NF-κB with increased production of IL-6 and TNF-α in adipocytes; 23,45 and induces the activation of p38, ERK, and JNK with increased expression of COX-2, IL-6 and MCP-1 in fibroblast cells. 46,47 Dietary supplementation with high-fat diet (HFD) or infusion of Liposyn II (a 20% triglyceride nonpyrogenic emulsion), lipid/heparin, soybean oil, lard oil, or fatty acids has been used to increase circulating FFA level in human and animal model studies.…”
Section: Long-chain Sfas Increase the Production Of Inflammatory Medimentioning
confidence: 99%
“…In the broad literature regarding this type of EFA (omega-3, omega-6, and omega-3/omega-6 ratio) and its relationship to cancer progression, several underlying mechanisms have been hypothesized. One of the most established mechanisms is an association between inflammatory pathways and the function of omega-3 and omega-6 FAs on the action of cyclooxygenase-2 (COX-2) in prostate cancer [ 134 , 135 , 136 ]. On the contrary, Gao et al [ 193 ] demonstrated that palmitate, a saturated FA, up-regulated COX-2 via NF-κB-dependent mechanism; consequently, COX-2-associated oxidative stress weakened endothelium-dependent relaxations in the mouse aortas.…”
Section: The Relationship Between Nutrition and Oxidative Stress Fmentioning
confidence: 99%
“…While saturated fats are the most inflammatory [50,61,62], overabundance of omega-6 (n-6) poly-unsaturated fats, such as those found in most cooking oils, have also been implicated in immune response through several mechanisms including effects on TLR4 [53] and serving as precursors for inflammatory mediators [63-67]. However, a recent review of human trials seems to undermine evidence supporting n-6 intake increases inflammation [68].…”
Section: Introductionmentioning
confidence: 99%